2018
DOI: 10.4103/ajm.ajm_70_17
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study: Comparing efficacy of 14-day triple therapy Clarithromycin versus levofloxacin on eradication of Helicobacter Pylori infection in Syrian population single-center experience

Abstract: Context:Goals: To compare the efficacy of standard triple therapy with clarithromycin versus triple therapy with levofloxacin for treatment of Helicobacter pylori-positive infection in a referral hospital in Damascus, Syria.Design:pilot prospective open-label randomized controlled trial.Subjects and Methods:Eighty treatment-naive patients who tested positive for H. pylori gastric infection were randomly assigned to one of two treatment groups with randomization ratio of 50/50. Group (A) was treated with clarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Helicobacter pylori is a gastric pathogen that colonises human stomach, leading to clinical manifestations of chronic gastritis, peptic ulcer disease, gastric adenocarcinoma and mucosa associated lymphoid tissue (MALT) lymphoma [1]. Current standard H. pylori eradication regime, also known as triple therapy, comprises two antibiotics (amoxicillin and clarithromycin or metronidazole) and a proton pump inhibitor (PPI) [5]. However, due to surging prevalence of clarithromycin and metronidazole resistance in H. pylori , the treatment success rate of either clarithromycin-based or metronidazole-based triple therapy is merely 80% or less in certain global regions [26].…”
Section: Introductionmentioning
confidence: 99%
“…Helicobacter pylori is a gastric pathogen that colonises human stomach, leading to clinical manifestations of chronic gastritis, peptic ulcer disease, gastric adenocarcinoma and mucosa associated lymphoid tissue (MALT) lymphoma [1]. Current standard H. pylori eradication regime, also known as triple therapy, comprises two antibiotics (amoxicillin and clarithromycin or metronidazole) and a proton pump inhibitor (PPI) [5]. However, due to surging prevalence of clarithromycin and metronidazole resistance in H. pylori , the treatment success rate of either clarithromycin-based or metronidazole-based triple therapy is merely 80% or less in certain global regions [26].…”
Section: Introductionmentioning
confidence: 99%
“…The result of levofloxacin containing therapy can be regarded as Grade D standard, while the result of bismuth-containing therapy can be regarded as Grade F as proposed recently [ 32 ]. The former results are better than our preceding study outcomes regarding the treatment of H. pylori [ 14 ]. Our results are agreeing with a meta-analysis by Essa et al and similar research by Federico et al Both studies showed that concomitant therapy is effective in the eradication of H.Pylori [ 26 , 33 ].…”
Section: Discussionmentioning
confidence: 55%
“…Researchers globally observe a decline in the rate of H pylori eradication following standard triple therapies, thus requiring a search for new therapeutic approaches [45–48]. This randomized clinical trial included 78 patients from an area of high prevalence (>15%) of clarithromycin and levofloxacin resistant helicobacter pylori strains [ 1 , 12 , 14 , 30 , 31 ]. Both concomitant and bismuth-containing quadruple therapies are recommended as alternative first-line treatment according to the previously mentioned guidelines, particularly in regions with a high prevalence of clarithromycin resistance [ 13 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other risk factors are genetic and family history of cancers such as hereditary nonpolyposis colorectal cancer (Lynch syndromes I & II) and familial adenomatous polyposis (FAP) [ 7 ], and none of them appear to be true in our case based on the history. Helicobacter Pylori infection is the most potently recognized risk factor for gastric adenocarcinoma; however, even after decades of infection, the only an insignificant proportion of infected subjects develop adenocarcinoma [ 8 ], and there is insufficient evidence to suggest the optimal age to begin eradication therapy [ 9 , 10 ], knowing that Helicobacter pylori infection eradication is difficult in Syria [ 11 , 12 ]. Early detection of a gastric tumor is critical in determining prognosis, and each of the following indicates metastatic gastric cancer: weight loss, anemia, Virchow nodes (left supraclavicular), Irish node (anterior axillary), and periumbilical (Sister Mary Joseph nodule).…”
Section: Discussionmentioning
confidence: 99%